2018
DOI: 10.1016/j.ehj.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, management and outcome of pulmonary embolism in Shahid Gangalal National Heart Centre, Kathmandu, Nepal

Abstract: Background and aimsPulmonary embolism (PE) is associated with a significant mortality and morbidity. We aim to study clinical profile, management and outcome of PE at Shahid Gangalal National heart Centre, Kathmandu, Nepal.MethodsIt was a retrprospective, single centre study, conducted from January 2015 to December 2016. Haemodynamics was used for risk Simplified, PESI score, predisposing factors, symptoms, clinical features at the time of admission, ECG features, echocardiogram, treatment received and the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study of 177 cases demonstrated that the proportion of ST-T changes on ECG was 49.15% in patients with PE ( 27 ). ST-T abnormalities are most common in precordial leads V 1 -V 3 on ECG in PE ( 28 ). Figure 4 also shows that inversion T-waves occurred in the right precordial leads, which might be associated with the right myocardial strain.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 177 cases demonstrated that the proportion of ST-T changes on ECG was 49.15% in patients with PE ( 27 ). ST-T abnormalities are most common in precordial leads V 1 -V 3 on ECG in PE ( 28 ). Figure 4 also shows that inversion T-waves occurred in the right precordial leads, which might be associated with the right myocardial strain.…”
Section: Discussionmentioning
confidence: 99%